2023
DOI: 10.3390/microorganisms11082110
|View full text |Cite
|
Sign up to set email alerts
|

The Probiotic Bacillus subtilis MB40 Improves Immunity in a Porcine Model of Listeriosis

Sean M. Garvey,
Nima K. Emami,
Justin L. Guice
et al.

Abstract: Probiotics for humans and direct-fed microbials for livestock are increasingly popular dietary ingredients for supporting immunity. The aim of this study was to determine the effects of dietary supplementation of Bacillus subtilis MB40 (MB40) on immunity in piglets challenged with the foodborne pathogen Listeria monocytogenes (LM). Three-week-old piglets (n = 32) were randomly assigned to four groups: (1) basal diet, (2) basal diet with LM challenge, (3) MB40-supplemented diet, and (4) MB40-supplemented diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 101 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…The intestinal microbiota is involved in the body’s metabolic function, immune system improvement, anti-infection effects, development, and behavior ( 27 , 28 ). Previous studies have shown that probiotics can effectively enhance the body’s anti-infective effect against pathogens ( 29 , 30 ). In this study, we found that preemptive oral administration of L. acidophilus effectively prevented C. p infection, which was reflected in reducing organ pathology, tissue damage, and bacterial load in the liver and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota is involved in the body’s metabolic function, immune system improvement, anti-infection effects, development, and behavior ( 27 , 28 ). Previous studies have shown that probiotics can effectively enhance the body’s anti-infective effect against pathogens ( 29 , 30 ). In this study, we found that preemptive oral administration of L. acidophilus effectively prevented C. p infection, which was reflected in reducing organ pathology, tissue damage, and bacterial load in the liver and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…The multifaceted effects of probiotic B. subtilis have been extensively studied in animal models. Recent research has evaluated the effects of different strains of B. subtilis on health maintenance and disease resistance in pigs [30,31], dogs [32][33][34][35], and chickens [36][37][38][39] in terms of the probiotic potential to enhance health in pets and health/productivity in farm animals. However, this review primarily focuses on recent research utilizing various strains of B. subtilis in human populations.…”
Section: Effects Of Different Strains Of Probiotic Bacillus Subtilis ...mentioning
confidence: 99%